Connectivity Analysis of Millimeter-Wave Device-to-Device Networks with Blockage - Haejoon Jung; In-Ho Lee (International Journal of Antennas and Propagation)
We consider device-to-device (D2D) communications in millimeter-wave (mm Wave) for the future fifth generation (5G) cellular networks. While the mm Wave systems can support multiple D2D pairs simultaneously through beamforming with highly directional antenna arrays, the mm Wave channel is significantly more susceptible to blockage compared to microwave; mm Wave channel studies indicate that if line-of-sight (LoS) paths are blocked, reliable mm Wave communications may not be achieved for high data-rate applications. Therefore, assuming that an outage occurs in the absence of the LoS path between two wireless devices by obstructions, we focus on connectivity of the mm Wave D2D networks. We consider two types of D2D communications: direct and indirect schemes. The connectivity performances of the two schemes are investigated in terms of (i) the probability to achieve a fully connected network PFC and (ii) the average number of reliably connected devices γ. Through analysis and simulation, we show that, as the network size increases, PFC and γ decrease. Also, PFC and γ decrease, when the blockage parameter increases. Moreover, simulation results indicate that the hybrid direct and indirect scheme can improve both PFC and γ up to about 35% compared to the nonhybrid scheme.